He's frequency–amplitude formulation for nonlinear oscillators using Jacobi elliptic functions - Alex Elías-Zúñiga; Luis Manuel Palacios-Pineda; Isaac H Jiménez-Cedeño; Oscar Martínez-Romero; Daniel Olvera Trejo (Journal of Low Frequency Noise, Vibration and Active Control)
In this work, the Duffing’s type analytical frequency–amplitude relationship for nonlinear oscillators is derived by using Hés formulation and Jacobi elliptic functions. Comparison of the numerical results obtained from the derived analytical expression using Jacobi elliptic functions with respect to the exact ones is performed by considering weak and strong Duffing’s nonlinear oscillators.